The Influence of Land Management on Soil Mite (Acari: Oribatida, Prostigmata, and Mesostigmata) Communities as Bioindicators for Environmental Conditions - Damayanti, Arina; Triyogo, Ananto; Musyafa (Jurnal Manajemen Hutan Tropika, 2023)
As a soil-living organism, soil mite presence is important for ensuring the sustainable land. Intensive management practices in forest land drive a change in its community structure. A field study was conducted in Wanagama Education and Research Forest I, Gunungkidul District, Yogyakarta Special Region Province, Indonesia, to assess the role and impact of the different forest management practices on the soil mite community. Soil samples from 15 representative soil sites were taken from the agroforestry, mixed-forest, and pioneer community forest. Collected individuals from August to October 2021 were taken by Berlese-Tullgenn Funnel and identified to morphospecies level. A total of 758 individuals of soil mites were recorded during the study period. Out of these, 21 individuals from agroforestry, 288 individuals from mixed-forest, and 449 individuals from pioneer community forest. Results of the study revealed the occurrence of 3 taxa from 36 morphospecies of oribatid mites occurred in the areas. The Shannon diversity indices of oribatid mites were 1.831, 1.424, and 0.867 in mixed-forest, agroforestry, and pioneer community, respectively. The similarity indices showed there was a similar diversity in agroforestry and mixed-forest, either in pioneer community. Through one-way ANOVA analysis, we stated that differences between of three management practices significantly affected soil mites, especially oribatida rather than prostigmata and mesostigmata.